2022
DOI: 10.1029/2022jf006745
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Landslides: How Stochastic Mass Wasting Shapes Topography and Influences Landscape Dynamics

Abstract: Landslides can produce sediment at rates that exceed the maximum rate of sediment generation by weathering processes (Dixon & von Blanckenburg, 2012), and can trigger a chain of processes that alter the pathways of sediment from source to sink (Fan et al., 2019). The continuously growing data realm of remotely sensed Earth observations and analytical measurements such as cosmogenic radionuclide (CRN) derived erosion rates helps to better understand the impact of mass movements on evolving surfaces (e.g., DeLis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…For example, channel steepness depends heavily on streamflow direction (Figure 9). Although this behavior is quite pronounced in our models, it might be less pronounced in models incorporating both landslides and sediment dynamics (Campforts et al, 2022) (i.e., due to increased stochasticity). In our models, the exposure of the weak unit also causes a gradual decline in the channel steepness of the strong unit (Figures 11 and S8).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…For example, channel steepness depends heavily on streamflow direction (Figure 9). Although this behavior is quite pronounced in our models, it might be less pronounced in models incorporating both landslides and sediment dynamics (Campforts et al, 2022) (i.e., due to increased stochasticity). In our models, the exposure of the weak unit also causes a gradual decline in the channel steepness of the strong unit (Figures 11 and S8).…”
Section: Discussionmentioning
confidence: 60%
“…Although this behavior is quite pronounced in our models, it might be less pronounced in models incorporating both landslides and sediment dynamics (Campforts et al, 2022) (i.e., due to increased stochasticity).…”
Section: Depictions Of Contact Advection and Topographic Advectionmentioning
confidence: 68%
See 1 more Smart Citation
“…We cannot exclude the possibility that the shift to highly depleted organic δ 2 H n C29 values reflect an increase in the proportion of high-elevation organic matter due to nonuniform erosion processes affected observed δ 2 H n C29 values. Hillslope processes such as landslides that produce sediment from high-elevation regions are likely to become more frequent as the height of an orogen increases ( 36 , 39 , 40 ). The high energy system represented by the conglomerates may capture a shift to greater mass wasting/erosion from these high-elevation regions of the orogen.…”
Section: Discussionmentioning
confidence: 99%
“…Stock and Dietrich (2006) formulated a possible debris‐flow incision model, but they also emphasized the importance of improving parameterizations for debris‐flow dynamics within landscape evolution models to work toward a validated debris‐flow GTL. Some works have found that it is possible to produce longitudinal profiles with slope‐invariant steepland valley bottoms by using modified versions of fluvial GTLs such as the stream power incision model that incorporates episodic fluvial floods (e.g., DiBiase & Whipple, 2011; Lague, 2014; Lague & Davy, 2003), by placing steep valleys under the control of hillslope processes (e.g., DiBiase et al., 2012; Ouimet et al., 2009), or including stochastic bedrock landsliding in landscape evolution models (e.g., Campforts et al., 2022). Other processes that may result in deviations from power‐law slope‐area scaling include lower entrainment thresholds required to transport sediment at steep slopes and low drainage areas (e.g., Lamb et al., 2008; Prancevic et al., 2014; Recking, 2009), rapid weathering on steep slopes as topographic stresses produce bedrock fractures (e.g., Li & Moon, 2021; Moon et al., 2017; Neely & DiBiase, 2020; St. Clair et al., 2015), and downstream changes in the width of geomorphically effective flows, including water‐dominated floods and debris flows (Alessio et al., 2021; Neely & DiBiase, 2023; Yanites, 2018).…”
Section: Introductionmentioning
confidence: 99%